Heme Oxygenase Induction Suppresses Hepatic Hepcidin and Rescues Ferroportin and Ferritin Expression in Obese Mice. (14th September 2017) - Puri, Nitin; Arefiev, Yevgeniy; Chao, Robert; Sacerdoti, David; Chaudry, Hibba; Nichols, Alexandra; Srikathanan, Krithika; Nawab, Athar; Sharma, Dana; Lakhani, Vishal Hari; Klug, Rebecca; Sodhi, Komal; et al.
Abstract : Hepcidin, a phase II reactant secreted by hepatocytes, regulates cellular iron levels by increasing internalization of ferroportin-a transmembrane protein facilitating egress of cellular iron. Chronic low-grade inflammatory states, such as obesity, have been shown to increase oxidative stress and enhance hepcidin secretion from hepatocytes and macrophages. Heme-heme oxygenase (HO) is a stress response system which reduces oxidative stress. We investigated the effects of HO-1 induction on hepatic hepcidin levels and on iron homeostasis in hepatic tissues from lean and obese mice. Obese mice exhibited hyperglycemia (p < 0.05 ); increased levels of proinflammatory cytokines (MCP-1, IL-6, p < 0.05 ); oxidative stress (p < 0.05 ); and increased hepatic hepcidin levels (p < 0.05 ). Enhancement of hepcidin was reflected in the reduced expression of ferroportin in obese mice (p < 0.05 ). However, this effect is accompanied by a significant decline in ferritin expression. Additionally, there are reduced insulin receptor phosphorylation and attenuation of metabolic regulators pAMPK, pAKT, and pLKB1. Cobalt protoporphyrin- (CoPP-) induced HO-1 upregulation in obese mice reversed these alterations (p < 0.05 ), while attenuating hepatic hepcidin levels. These effects of CoPP were prevented in obese mice concurrently exposed to an inhibitor of HO (SnMP) (p < 0.05 ). Our results highlight a modulatory effect of HO on iron homeostasis mediated through the suppression of hepatic hepcidin.